Examining the Acceptance of and Resistance to Evolutionary Psychology - Carey J. Fitzgerald; Mitchell B. Whitaker (Evolutionary Psychology, 2010)
The field of psychology remains a divided one. Several different sub-disciplines (e.g., developmental, cognitive, behaviorism, social, etc.) form what could be a unified scientific area. However, there is no widely accepted theory of unification. Charles Darwin once theorized that evolutionary theory would change the foundation of psychology; but over the years, evolutionary psychology has been met with hostile resistance from some of the prominent psychologists within the other sub-disciplines. Yet in recent years, all of the divided sub-disciplines of psychology have been slowly implementing evolutionary principles into their literature and research. This slow integration of evolutionary psychology into the other sub-disciplines indicates the possibility of a unified psychology with evolution as its foundation. This paper briefly reviews the literature within each major sub-discipline of psychology to show their implementation of evolutionary psychological theories, indicating the possibility of evolutionary psychology becoming the unifying paradigm upon which the entire field of psychology can be based. A call for action to continue this process is also discussed.